Evaluación del grado de compactación en la red de caminos vecinales de Riobamba comparando métodos convencionales y alternativos in situ - Paredes Leon, Luis Carlos (2024)
Local roads, according to (NEVI-12, 2012) indicates that these are those conventional roads that go from rural roads not included in maps, which can be destined to receive traffic for domestic use of different populations, areas of agricultural activities. , livestock and access to tourist areas. The general objective of this research was to evaluate the degree of compaction of the local roads of the Riobamba canton through comparison of laboratory values and field measurements with non-conventional equipment, taking into account their importance within the economic development of the canton. The degree of compaction is an important soil parameter that indicates the resistance and deformation required to increase the stability of natural soils. Soil compaction is a process that is carried out mechanically and through which it is expected to adapt the characteristics of the soil, among which are: resistance to shear stress, compressibility, permeability, among others. Through compaction, soil particles are forced together by reducing the void ratio. The conventional methods carried out are the sand cone test and the modified proctor, and the alternative methods are tests that were executed with the EDG and Geogauge equipment. Data on densities, humidity and compaction of the soil were taken through the alternative tests and were compared with the data from the conventional tests. The research carried out is quantitative, with an experimental design, which was carried out with a total population of 110 kilometers of local roads within the urban area of the Riobamba canton, with the help of georeferencing software (ArcGIS) and sampling non-probabilistic, resulted in 10 control points as a total sample within these paths, these control points were analyzed using the aforementioned methods. According to (NEVI-12, 2012), the degree of compaction of a road soil must be 95% or greater. From the data obtained with alternative methods, only 20% of the total sample analyzed meets the degree of compaction exposed in the norm, thus leaving the remaining 80% with a compaction less than the imposed limit. On the other hand, by estimating data from conventional methods, 40% of the analyzed sample meets the aforementioned. According to the statistical adjustment of the alternative methods (EDG), a confidence level of 70% was achieved in the data collection in the different trials. This is reflected in the similarity of the values obtained with the different methods in terms of densities, humidity and degrees of compaction of the soils tested. This variation between the results of the conventional and alternative methods is due to the values of the dry densities and maximum dry densities that exist at each control point.